Parental belief in ‘healthy risk’ lead to fewer child accidents and injuries: fact or fiction? - Marryat, Louise; Frank, John (International Journal of Population Data Science, 2018)
There has been a substantial amount of debate around the role of parental risk aversity in children's health and wellbeing, with results suggesting that, whilst in the short-term, parents may ensure their children's safety, in the longer-term, children's psychological well-being may be compromised, and a lack of activity may result in a range of other poorer outcomes (Little and Wyver, 2008). Whilst some approaches to risk can be seen as extreme, there appears to be a role for healthy, positive risk in parenting (Bundy et al., 2009). Studies to date in this area have mostly comprised a mixture of survey and observational data, with little evidence on the relationship between parental risk aversity and child outcomes, such as accidents and injuries. The current study explores these associations, using data exploring parental perceptions of risk, taken at ages 3 and 5, from the Growing Up in Scotland birth cohort study, linked with administrative hospital data about child accidents and injuries up to age 11. This paper will investigate results on associations between parental perceptions of risk, and child accidents and injuries, as well as exploring whether these impacts change through early to middle childhood, and whether they differ by socio-economic classification.